2012
DOI: 10.1002/hbm.22040
|View full text |Cite
|
Sign up to set email alerts
|

“Feeling” others' painful actions: The sensorimotor integration of pain and action information

Abstract: Sensorimotor regions of the brain have been implicated in simulation processes such as action understanding and empathy, but their functional role in these processes remains unspecified. We used functional magnetic resonance imaging (fMRI) to demonstrate that postcentral sensorimotor cortex integrates action and object information to derive the sensory outcomes of observed hand–object interactions. When subjects viewed others’ hands grasping or withdrawing from objects that were either painful or nonpainful, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 80 publications
13
62
0
Order By: Relevance
“…A similar principle could apply to lOT, a multisensory region responding both to tactile stimulation (Hagen et al, 2002) and to the sight of touch (Ebisch et al, 2008). This is consistent with the proposal that multimodal circuits in the brain driving oneʼs actions and sensations can ground an experience-based perception and generate expectations of othersʼ sensations during social interaction based on embodied simulation (Morrison et al, 2013;Gallese & Sinigaglia, 2011;Sebanz et al, 2006;Wilson & Knoblich, 2005;Gallese, 2003;Gallese & Goldman, 1998). …”
Section: Active Interpersonal Touch Mediated By An Objectsupporting
confidence: 80%
See 3 more Smart Citations
“…A similar principle could apply to lOT, a multisensory region responding both to tactile stimulation (Hagen et al, 2002) and to the sight of touch (Ebisch et al, 2008). This is consistent with the proposal that multimodal circuits in the brain driving oneʼs actions and sensations can ground an experience-based perception and generate expectations of othersʼ sensations during social interaction based on embodied simulation (Morrison et al, 2013;Gallese & Sinigaglia, 2011;Sebanz et al, 2006;Wilson & Knoblich, 2005;Gallese, 2003;Gallese & Goldman, 1998). …”
Section: Active Interpersonal Touch Mediated By An Objectsupporting
confidence: 80%
“…For example, in a previous study, we found that aIPL not only activates in response to tactile input, but also for the mere observation of another individual being touched (Ebisch et al, 2008). Furthermore, Morrison et al (2013) postulated that aIPL, together with PostCG, may subserve the anticipation of the sensory consequences of observed hand-object interactions through the integration of action information and external information about the object. Here, we extend these findings by showing that aIPL and PostCS also activate in anticipation of active interpersonal touch without the need for any sensory input.…”
Section: Active Interpersonal Touch Mediated By An Objectmentioning
confidence: 71%
See 2 more Smart Citations
“…For that reason, the control videos consisted of a hand approaching another hand without holding an object. Morrison, Tipper, Fenton-Adams, and Bach (2013) showed that separate somatosensory regions responded more strongly when the observed action targeted noxious rather than neutral objects, irrespective of the action carried out with them. This suggests an encoding of tactile object properties independent of action properties.…”
Section: Discussionmentioning
confidence: 99%